Zukünfte. Aufstieg und Krise der Zukunftsforschung 1945-1980 - Seefried, Elke 1971- (Quellen und Darstellungen zur Zeitgeschichte, 2015)
After 1945, new methods and tools for forecasting the future grew out of the dynamic developments that were taking place in science and technology. Conceptions of futures research or futures studies as approaches to forecasting, planning and envisaging the future grew out of transnational circulations of knowledge in the 1950s and 1960s. The futures field was epitomized by the perception of many possible futures to be forecast and shaped. However, during the 1970s, the limits of envisioning the future became increasingly evident. This book as the first comprehensive study on the topic focuses on the futures field in Western industrialized countries – particularly the USA and West Germany – but also takes the socialist states and global networks into its ambit